Scooby-Doo movie ultimate joke book - Dow, T. E. J.; Dewin, Howard (New York : Scholastic Inc., 2002)
Features riddles, gags, and knock-knocks from all your Mystery, Inc. favorites--Fred, Daphne, Velma, Shaggy, and Scooby-Doo--guaranteed to keep you giggling.
"Over 150 groovy jokes based on the movie from Warner Bros. Pictures!"--Cover.
RL:3.
008-012.
Keywords: Wit and humor; Scooby-Doo (Fictitious character) -- Wit and humor; Jokes; Riddles; Scooby-Doo (Motion picture); Scooby-Doo (Fictitious character) -- Humor; Children's stories; Movie novels; Radio and television novels